The effects of plyometric and resistance training on linear sprinting speed and repeated sprinting ability of youth players in Ethiopia - Chekle, Belayneh (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The study investigated the effects of resistance training, plyometric training, and resistance and plyometric training combined on linear-speed and repeated sprinting ability (RSA) of youth soccer players. The authors used a randomized block design, randomly assigning thirty-six male soccer players (aged 18 ± 1.212 years, with a body weight of 57 ± 3.580 kg) to one of three groups: plyometric exercise, combined plyometric and resistance exercise, and resistance exercise. The authors analyzed each group's performance gains by comparing the pretest and post-test performance scores using paired sample t-test. All three training groups achieved significant performance gains in linear speed and repeated sprinting ability (RSA) (p<0.05). The plyometric and combined groups achieved higher linear-speed performance than the resistance training group (p<0.05). However, there was no significant difference among the three groups in repeated-sprinting-ability scores (p>0.05). In conclusion, plyometric and combined exercises are important training methods to impact speed for soccer players. Thus, when the focus is on soccer-specific linear speed and repeated sprinting ability, coaches and their training programs should emphasize methods that incorporate appropriate plyometrics and resistance training. This fitness-oriented training has to be considered in line with the technical and tactical trainings as they are helpful to get the most from the players’ technical-tactical qualities.